Intra-regional Wage Inequality in Portugal - Pereira, João (2015)
Studies on intra-regional inequality are scarce, particularly for European countries. This paper aims at further investigating inequality by focusing on wage differences within regions. We consider the case of Portugal, which is considered one of the countries with the highest level of economic inequality. In particular, we analyse the evolution of intra-regional wage inequality between 1995 and 2005, employing a quantile-based decomposition method. Our results show that wage inequality evolution has been different across the various regions, increasing in some regions and decreasing in others. Different changes in the workforce composition explain these diverse developments.